Urinary N-acetyl-β-d-Glucosaminidase Levels are Positively Correlated With 2-Hr Plasma Glucose Levels During Oral Glucose Tolerance Testing in Prediabetes - Ouchi, Motoshi; Suzuki, Tatsuya; Hashimoto, Masao; Motoyama, Masayuki; Ohara, Makoto; Suzuki, Kazunari; Igari, Yoshimasa; Watanabe, Kentaro; Nakano, Hiroshi; Oba, Kenzo (Journal of clinical laboratory analysis, 2012)
Background Urinary N‐acetyl‐β‐D‐glucosaminidase (NAG) excretion is increased in patients with impaired glucose tolerance (IGT). This study investigated when during the oral glucose tolerance test (OGTT) the plasma glucose, urine glucose, and insulin levels correlate most strongly with urinary N‐acetyl‐β‐d‐glucosaminidase (NAG) levels in prediabetic subjects. Methods The OGTT was administered to 80 subjects who had not yet received a diagnosis of diabetes mellitus (DM) and in whom HbA1c levels were ≤6.8% and fasting plasma glucose levels were <7.0 mmol/l. Forty‐two subjects had normal glucose tolerance (NGT), 31 had impaired glucose tolerance (IGT), and 7 had DM according to World Health Organization criteria. Serum levels of cystatin C, the estimated glomerular filtration rate, the urinary albumin‐to‐creatinine (Cr) ratio, urinary and serum β2‐microglobulin, and urinary NAG were measured as markers of renal function. Results NAG levels were significantly higher in subjects with DM and in subjects with IGT than in subjects with NGT. No significant associations were observed between glycemic status and other markers of renal function. Multiple linear regression analysis showed that the NAG level was positively correlated with plasma glucose levels at 120 min of the OGTT and was associated with the glycemic status of prediabetic patients. Conclusion These results suggest that postprandial hyperglycemia is an independent factor that causes renal tubular damage in prediabetes patients.